The Clinical Application of Superb Microvascular Imaging in Evaluating Thyroid Related Diseases: A Systematic Review - Ji, Jiaqi; Tang, Enyu; Wang, Ya'ni; Shi, Xinlong (Journal of Clinical Ultrasound, 2024)
This article reviews all published articles on the application of superb microvascular imaging (SMI) technique in thyroid related diseases before December 31, 2023. SMI, a recently developed ultrasound imaging modality, could display microvascular information by eliminating clutter and preserving low flow signals. Most studies used SMI to help diagnose malignant thyroid nodules and concluded that SMI performed better than color Doppler imaging and power Doppler imaging. At present, there is no consensus when depicting the morphology of vascularity of thyroid nodules (TNs). This problem may be solved by quantitative SMI which makes it possible to quantitatively evaluate the vascularity of TNs. SMI is also applied to evaluate cervical lymph node or thyroid inflammatory diseases. Although, SMI has some limitations, such as no standard for the normal perfusion patterns, and it has a broad application prospect in the diagnosis and management of thyroid related diseases.
CRIS-Team Scopus Importer:2024-10-18
Keywords: papillary thyroid carcinoma; superb microvascular imaging; thyroid diseases